Exploring Leadership Models in Islamic Education: A Comparative Study of Mono and Dual Leadership Structures in East Java Pesantren - Zainal Abidin; Moh. Dasuki; Abdul Karim; Khairul Umam; Shoni Rahmatullah Amrozi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
Grounded in leadership theory within educational and socio-religious institutions, this study examines three critical aspects of leadership in pesantren (Islamic boarding school): the formation of formal and informal structures; the role of family, foundations, and symbols of authority in reinforcing internal stability and leadership legitimacy; and the consequences of leadership models on moderation, institutional openness, and adaptability of pesantren. A qualitative approach was employed, involving in-depth interviews, participatory observation, and document analysis at Pesantren Miftahul Ulum and Pesantren Kiai Syarifuddin in East Java. Data and findings were analyzed through symbolic and socio-cultural lenses. The results indicate that the mono leadership model generates a centralized and rapid decision-making process heavily reliant on the personal authority of the Kiai. In contrast, the dual leadership model emphasizes collective deliberation through family forums and foundation structures, fostering an inclusive and adaptive organizational culture. Spiritual symbols and the informal role of family members were also key elements in maintaining value continuity and internal stability in both models. This study offers a new analytical contribution by highlighting how differing leadership typologies in pesantren not only influence internal governance but also shape the development of democratic and moderate Islamic education practices within changing socio-religious contexts.